Most Potent Herbal Remedy for Arthritis - Aishwarya Shivkumar Patil; S. V. Pimpale; B. S. Wakure (Novel Aspects on Pharmaceutical Research Vol. 5, 2023)
India indeed has a rich history and tradition in the field of medicine, particularly in Ayurveda. Ayurvedic medicine has been gaining popularity in recent years due to its effectiveness in treating various diseases, including autoimmune disorders like rheumatoid arthritis. The combination of herbal drugs such as ashwagandha, safed musli, mahayogiraj guggul, and maharasandi kwath has been clinically proven to have anti-inflammatory, analgesic, and anti-arthritic activities when used alone. Combining these potent herbs can provide a powerful treatment for rheumatoid arthritis. It is important to note that inflammation can occur due to physical injury or faulty metabolism of the body. According to Ayurveda, faulty metabolism produces Aam or toxins that lead to an imbalance in the body’s three main pillars - vata, pitta, and kapha. ROS, or Reactive Oxygen Species, are highly unstable compounds that play a role in the progression of inflammatory disorders. The body’s complex antioxidant defense system normally controls ROS levels, but overproduction of ROS and/or inadequate antioxidant defense can lead to oxidative stress and result in several clinical disorders. Therefore, it is important to maintain a healthy lifestyle, including a balanced diet and stress management, to prevent the buildup of toxins and maintain a healthy antioxidant defense system.